Contagious caprine pleuropneumonia: A review of the global situation with a special reference to Oman - Haytham Ali; Aida Altubi; Mahmoud El-Neweshy; Elshafie Elshafie (German Journal of Veterinary Research)
Contagious caprine pleuropneumonia (CCPP) is a severe infectious disease caused by Mycoplasma capricolum subsp. capripneumoniae (Mccp) and infects goats, sheep, and wild ruminants. CCPP is characterized by high morbidity and mortality rates reaching up to (100% and 80%), respectively. The disease affects goat farming around the globe in more than 30 countries, particularly in Asia, the Middle East, and Africa. CCPP is manifested in peracute, acute, or chronic forms. The general characteristic clinical signs of the disease are rapid, painful, and labored respiration, dyspnea, nasal discharge, coughing, hyperthermia (41°C), anorexia, emaciation, and abnormal posture. Lesions induced by CCPP are restricted to the pleural cavity in the form of unilateral serofibrinous, pleuropneumonia, accumulation of fluid in the chest cavity, lung congestion, hepatization, formation of adhesion to the pleural coastal, and swollen mediastinal and bronchial lymph nodes. Disease diagnosis encompasses a range of methods, including bacterial culture, isolation, and identification, pathological, serological, and molecular tests. The present review provides an overview of the historical perspective, epidemiological factors, and recommended diagnostic and control strategies for CCPP in Oman.